Corrosion inhibition efficiency of heavy alkyl benzene derivatives for carbon steel pipelines in 1 M HCl - A.M. Al-Sabagh; H.M. Abd-El-Bary; R.A. El-Ghazawy; M.R. Mishrif; B.M. Hussein (Egyptian Journal of Petroleum)
The corrosion inhibition process of carbon steel in 1 M HCl by octadecylbenzene sulfonic acid (H) and their three ester derivatives (H1, H2, and H3) were studied. The esters were quaternized by n-butyl bromide to get (H1Q, H2Q, and H3Q). These products have been investigated as corrosion inhibitors using weight loss and potentiodynamic polarization measurements. From the obtained results it was found that, the inhibition efficiency increases with increasing the inhibitor concentration and the efficiency of the inhibitors were ranked as (H3Q > H2Q > H1Q > H3 > H2 > H1 > H). The adsorption of the inhibitors on the carbon steel surface obeyed the Langmuir’s adsorption isotherm. The effect of temperature on the corrosion behavior in the presence of the inhibitors was studied in the temperature range of 303–333 K. The associated activation energy of corrosion and other thermodynamic parameters such as enthalpy (ΔH∗), entropy (ΔS∗) of activation, adsorption equilibrium constant (Kads) and standard free energy of adsorption (Δads0) were calculated to elaborate the corrosion inhibition mechanism. Potentiodynamic polarization studies indicated that, the studied inhibitors are mixed type inhibitors.